Meet the expert : selected experts on AI in healthcare. (Meet the expert (O'Reilly Media, Inc.), 2020)
"Join us for a new Meet the Expert series from Intel. Each event will feature three short back-to-back presentations from Intel partners from industries including healthcare, banking and finance, retail, security, and more. Learn how companies are solving real-world business problems across a variety of AI workloads and how enterprise customers are using these solutions today."--Resource description page